Framing the diagnosis and treatment of absolute uterine factor infertility: Insights from in-depth interviews with uterus transplant trial participants. Issue 1 (2nd January 2019) - Richards, Elliott G.; Agatisa, Patricia K.; Davis, Anne C.; Flyckt, Rebecca; Mabel, Hilary; Falcone, Tommaso; Tzakis, Andreas; Farrell, Ruth M.
Abstract: Background: Despite procedural innovations and increasing numbers of uterus transplant attempts worldwide, the perspectives of uterus transplant (UTx) trial participants are lacking.Methods: We conducted a mixed-methods study with women with absolute uterine factor infertility (AUFI). Participants included women who had previously contacted the Cleveland Clinic regarding the Uterine Transplant Trial and met the initial eligibility criteria for participation. In-depth interviews were conducted in conjunction with FertiQoL, a validated and widely used tool to measure the impact of infertility on the quality of life of infertility patients.Results: All ( n  = 19) rated their overall health as good; some experienced grief and social isolation. AUFI is a life-framing experience that influences acceptance by family, partners, peers, and one's self. UTx is a means to gain control of reproductive autonomy. UTx allows family-building and the ability to play an active role in prenatal health and well-being. Establishing and maintaining a supportive relationship is a key issue of AUFI and when considering UTx. Risks of UTx are perceived relative to risks to self/child/family posed by adoption/surrogacy. Participants had no overall preference regarding living or deceased donor.Conclusions: The ways in which women with AUFI conceptualize this condition in their lives and choices around UTx and participating in a study of the procedure are multifaceted and textured. These perspectives are critical to understanding its ethical, legal, and social implications.